Evaluation of Ã¢â¬ÅJumat PintarÃ¢â¬Â Program in Reducing the Incidence of Anemia in Young Women in Sukoharjo, Indonesia - Pratiwi, Ayudhia; Suryani, Nunuk; Indarto, Dono (Journal of Maternal and Child Health, 2016)
Background: Anemia is iron deficiency in the body which gives a negative impact. Anemia in the short term can lead to vulnerable young women experience a decline in achievement of learning at school. While long-term, sustained anemia from adolescence until the pregnant can lead to complications of bleeding to death and in Sukoharjo, Jumat Pintar implementation prevents the incidence anemia especially in young women. The activity encouraged from this policy is the giving of Fe tablet. The evaluation was conducted to assess the performance of the implementation of the policy of running and achievements obtained in accordance with the original purpose. This study was aimed to evaluate the implementation of Jumat Pintar program in lowering the incidence of anemia of young women.Subject and Methods: This was a qualitative study, was conducted in September-October 2016 in Sukoharjo. A total of 20 samples were selected by using purposive sampling technique. The data was collected using in depth interviews, observation and study of documentation. The data were analyzed using the interactive analysis techniques to compare the data obtained with data triangulation.Results: The execution of Jumat Pintar at stages of planning activities, the determination of the amount of goals and services granting Fe tablet was in adherence with the standard procedures of implementation. The stage of the expansion of the network of independent outlets and stages of monitoring and oversight have not run optimally. The scope of consumption of Fe tablet is not can be traced and decrease in the numbers of Genesis anemia in teenagers does not represent the entire area. The main constraints implementation comes from the absence of a legal umbrella agreement work, lack of financial support from various parties, the low commitment of the education sector, and low awareness of the goal.Conclusion: The implementation of Jumat Pintar is running optimally. The formation of independent outlets have yet to be implemented at each high school in Sukoharjo Regency, the absence of funding sources and still low level of involvement of target.Keywords: anemia, the movement of young women, the evaluation of the implementation of Jumat Pintar program.Correspondence:ÃÂ Ayudhia Pratiwi. School of Public Health, Sebelas Maret University, Surakarta.Journal of Maternal and Child Health (2016), 1(1): 25-33https://doi.org/10.26911/thejmch.2016.01.01.05ÃÂ